2015
DOI: 10.1016/j.jecp.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural evidence for multimodal motherese: Asian Indian mothers’ adaptive use of synchronous words and gestures

Abstract: In a quasi-experimental study, twenty-four Asian-Indian mothers were asked to teach novel (target) names for two objects and two actions to their children of three different levels of lexical-mapping development, pre-lexical (5–8 months), early-lexical (9–17 months), and advanced-lexical (20–43 months). Target (N = 1482) and non-target (other, N = 2411) naming was coded for synchronous spoken words and object motion (multimodal motherese) and other naming styles. Indian mothers abundantly used multimodal mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 62 publications
(123 reference statements)
5
42
0
Order By: Relevance
“…This is because in free‐flowing toy play, the object held by one's hand(s) at a moment usually aligns well with their focus of attention and therefore provides a reliable and complementary (in addition to gaze) measure of one's attentional focus through manual action (Bambach et al, ; Yoshida & Smith, ). Previous studies have shown that moving an object while talking about it at the same time can increase the saliency of the object and facilitate young children's learning of object names (Gogate, Bolzani, & Betancourt, ; Gogate, Maganti, & Bahrick, 2; Lund & Schuele, ). It is very likely that moving an object attracts children's attention more than simply holding an object still and makes it easier for young children to follow in and look at the object of parents' focus of attention.…”
Section: Discussionmentioning
confidence: 99%
“…This is because in free‐flowing toy play, the object held by one's hand(s) at a moment usually aligns well with their focus of attention and therefore provides a reliable and complementary (in addition to gaze) measure of one's attentional focus through manual action (Bambach et al, ; Yoshida & Smith, ). Previous studies have shown that moving an object while talking about it at the same time can increase the saliency of the object and facilitate young children's learning of object names (Gogate, Bolzani, & Betancourt, ; Gogate, Maganti, & Bahrick, 2; Lund & Schuele, ). It is very likely that moving an object attracts children's attention more than simply holding an object still and makes it easier for young children to follow in and look at the object of parents' focus of attention.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the regularities in activity around caregiver speech are provided by caregivers' paralinguistic 115 actions. During infants' first year, caregivers' object-name productions are embedded in multimodal behavioral complexes featuring synchronous speech and object motion (Gogate, Bahrick, & Watson, 2000;Gogate, Maganti, & Bahrick, 2015;Matatyaho & Gogate, 2008). In one study, mothers taught 6-to 8-month-old infants two novel object words.…”
Section: Correlates Of Caregiver Speechmentioning
confidence: 99%
“…Contingent responses to infant babbling promote and shape speech development (Goldstein, King, & West, 2003). Mapping words to objects entails coordinating visual and auditory information, and parents scaffold learning by timing verbal labels with gaze and/or object movement (Gogate, Bahrick, & Watson, 2000; Gogate, Maganti, & Bahrick, 2015; Gogate, Walker-Andrews, & Bahrick, 2001; Gogate & Hollich, 2010). Parents also exaggerate visual and auditory prosody to highlight meaning bearing parts of the speech stream (“multimodal motherese”; Gogate et al, 2000, 2015; Kim & Johnson, 2014; Smith & Strader, 2014).…”
mentioning
confidence: 99%